Material selection in hot shaping molds of titanium alloys - Eker, Aysegul Akdogan; Avci, Ali; Aydin, Hakan; Aydogan, Cahit Sertac; Erol, Emre (ELSEVIER SCIENCE BV, 2020)
Titanium alloys are widely employed in industries especially in aviation sector due to their high strength, light weight, superior corrosion resistance and other specific characteristics. Titanium alloys with superplastic properties are shaped by different methods. The present study aims at selecting the mold materials used for the shaping of titanium parts with a maximum thickness of 2 mm at 500-700 degrees C. In the selection of mold material, the chemical composition of the alloy, process temperature, thermal fatigue cracks and the number of parts to be shaped are taken into consideration. In this study, distortion and surface oxidation are investigated for the molds used in the isothermal hot shaping of titanium parts in order to select the most suitable mold material. For this purpose, 7 different hot work tool steels and 3 stainless steel types, which are easily available in the market, have been selected. Due to the titanium shaping operations for 2-3 hours at 700 C degrees, samples were kept in the oven at 700 degrees C for 30, 60, 120 minutes respectively, depending on the shape of the part. Furthermore, the oxide layer formed on the surface was observed separately for each cycle. The heating-cooling cycle was repeated 5 times for 120 minutes to determine the structural changes that may occur on the mold material surface. At the end of the process, the hardness and surface roughness of the mold materials were measured and corrosion resistance was calculated. By analyzing the macro and microstructure of the internal structures, appropriate mold materials were determined. (C) 2020 The Authors. Published by Elsevier B.V.
Keywords: Materail Selection; Corrosion; Hot Work Steels; BEHAVIOR; Engineering; Metallurgy & Metallurgical Engineering